Dialogue on the teaching-learning relationship in the discipline of Physics with high school students (Research, Society and Development, 2021)
Culturally, a view was created in which Physics is a discipline considered complex both in High School and in Higher Education. Therefore, this study aimed to assess the perception of students about the teaching-learning relationship in the discipline of Physics and identify the problems mentioned by them that somehow hinder this relationship. The research is of a mixed type, and data were obtained through a questionnaire containing 6 objective and discursive questions, which was applied personally and individually to high school students enrolled in the 3 main public schools in the city of Confresa-MT, the questionnaire was applied to 263 students between the months of April and October 2019. Through data analysis, it was possible to verify that 58.17% of the students rate the teaching-learning process as great or good and some students related the quality of the process with the way the teacher teaches classes, even considering that to have Success in this process requires that the whole environment is in harmony, among the main problems mentioned are: teacher's difficulty in explaining the contents, distractions, lack of interest and bad behavior in the classroom in general. As points to improve the quality of the process, they mentioned: changing the content explanation method, more dynamic classes, and more interaction between teacher and student.